Method for producing high-purity chromium metal from waste chromium-containing refractory material by using carbon reduction method

By using carbon reduction method and specific additives in the treatment of waste chromium-containing refractory materials, combined with magnetic separation, acid impurity removal and electroslag remelting technologies, the purity and recovery rate of metal chromium have been successfully improved, the problem of difficulty in removing impurities in traditional methods is solved, and the risk of safety and environmental protection is reduced.

CN119824250AInactive Publication Date: 2025-04-15HUNAN HUAZAN TECH CO LTD

Patent Information

Application Number
CN202510299439.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When traditional methods deal with waste chromium-containing refractory materials, it is difficult to effectively remove impurities, resulting in low purity and recovery of metal chromium and pose safety and environmental risks.

Method used

Carbon reduction method combined with magnetic separation, acid leaching, two-stage heating reduction and electroslag remelting technology is used to extract high-purity metal chromium from waste chromium-containing refractory materials. By selecting yttrium stabilized zirconium oxide and lanthanum fluorine as additives, the melting point of the slag phase is reduced and the efficiency of slag gold separation is improved.

Benefits of technology

The production of metal chromium with high purity (98.9%-99.4%) and high recovery rate (82.2%-82.5%) has been achieved, reducing landfill and safety risks, and improving the purity and recycling efficiency of the product.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for producing high-purity metal chromium from waste chromium-containing refractory materials by using a carbon reduction method, belongs to the technical field of general industrial solid waste resource environment-friendly comprehensive utilization and metal smelting, and particularly relates to a method for producing the high-purity metal chromium from the waste chromium-containing refractory materials by performing crushing magnetic separation, acid leaching impurity removal, carbon reduction, slag-metal separation and electroslag refining processes on the waste chromium-containing refractory materials. The purity of the finally produced metal chromium reaches 98.9%-99.4%, and the chromium recovery rate reaches 82.2%-82.5%. Wherein yttria-stabilized zirconia and lanthanum oxyfluoride are selected as additives, it is accidentally found in the research process that the lanthanum oxyfluoride and zirconia are combined for use to have a synergistic effect, and during specific combination, lanthanum oxyfluoride and zirconia can form a La-Zr-O-F composite melt, so that the slag-gold separation efficiency is remarkably improved; and further, the purity of the final product chromium metal is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of general industrial solid waste resource utilization and metal smelting technology, and specifically is a method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method. Background Art

[0002] Various chromium-containing refractory materials, such as high-chrome bricks, magnesia-chrome bricks, chrome corundum, etc., are widely used in high-temperature containers or high-temperature kilns in the fields of petrochemicals, coal chemical industry, waste incineration power generation, glass production, non-ferrous metal smelting, aerospace, etc. They are also important basic materials for the implementation of most high-temperature industrial specialized and new processes and technologies. In the production and use of refractory materials, a large amount of waste refractory insulation materials will be generated. Among them, refractories with high magnesium oxide and chromium oxide content (such as high-chrome bricks, mainly composed of chromium oxide and aluminum oxide; and magnesia-chrome bricks, mainly composed of chromium oxide and magnesium oxide) have excellent slag erosion resistance and high strength in high temperature and acidic environments. They are irreplaceable refractory materials in high-temperature industrial kilns. After 1 to 2 years of use, they must be dismantled to prevent burning through the kiln, which will lead to the generation of a large amount of waste chromium-containing refractory materials.

[0003] The traditional disposal method of chromium-containing refractory materials is mainly to landfill them or crush them and mix them with new refractory materials for use as aggregates: 1. Chromium-containing refractory materials are different from general refractory materials. They contain Cr, which is extremely harmful to human body and environment. If the discarded chromium-containing refractory materials are not effectively disposed of, randomly piled or landfilled, they will slowly transform into hexavalent chromium in a short time, which will have a long-term impact on the surrounding groundwater and soil, and indirectly endanger human health.

[0004] 2. During the manufacturing and use process, waste materials undergo long-term high-temperature sintering in a high-temperature environment above 1300℃ to form a dense structure like corundum. When mixed with aggregates in the production process of new refractory materials, they may not be perfectly sintered into a eutectic with other raw materials, thus potentially affecting the new refractory materials. If used in high-temperature and high-pressure kilns with ultra-high temperature (1300-1800℃) and ultra-high pressure (3.0-6.5Mpa), it will bring great safety hazards. Moreover, the new refractory materials will become waste refractory materials after a period of use and will be crushed again and mixed into a new batch of new refractory materials. The vicious cycle will form a vicious circle, which will lead to serious safety and environmental risks. Summary of the invention

[0005] The present invention provides a method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method. The present invention aims to ultimately improve the purity and recovery rate of the recovered metallic chromium by improving a specific recovery process, especially improving and innovating additives in the carbon reduction method.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method, comprising the following steps: S1. Collect waste chromium-containing refractory materials and crush them to a particle size of 0.1-1 mm. After magnetic separation and impurity removal, a chromium-containing concentrate is obtained. After acid leaching and impurity removal, a chromium-rich raw material is obtained. S2, preparing a mixture of chromium-rich raw material, carbon powder, yttrium-stabilized zirconium oxide and lanthanum oxyfluoride; S3, pressing the mixture into pellets, and then adopting a two-stage heating reduction process to obtain a reaction product; S4, cooling the reaction product to 800-1000°C, and then preliminarily separating and removing the slag phase by gravity sedimentation, and subjecting the remaining metal phase to electroslag remelting and refining treatment to obtain refined metallic chromium, and completing the recovery of metallic chromium after cooling.

[0007] Furthermore, the waste chromium-containing refractory material described in S1 includes the following components in terms of mass percentage: Chromium 23.1%~23.5%; Magnesium 41.0% to 42.2%; Aluminum 4.7%~5.0%; Silicon 2.5% to 2.7%; Iron 2.0%~2.1%.

[0008] Furthermore, the acid leaching and impurity removal in S1 comprises the following steps: The chromium-containing concentrate is soaked in an acetic acid solution with a pH of 4.5 to 6.0 for 0.5 to 2 hours to obtain a de-impurity concentrate, and then the de-impurity concentrate is rinsed with deionized water until the washing water is neutral, and then dried at 80 to 100° C. for 12 hours to obtain a chromium-rich raw material.

[0009] Furthermore, the purity of the carbon powder in S2 is 99.5%; The purity of the yttrium-stabilized zirconia reaches 99.9%; The purity of the lanthanum fluoride oxide is 99%.

[0010] Furthermore, the mass ratio of the chromium-rich raw material, carbon powder, yttrium-stabilized zirconium oxide, and lanthanum oxyfluoride in S2 is 100:25-30:4.2-5.0:2.5-3.0.

[0011] Furthermore, the diameter of the pellets in S3 is 20 to 50 mm.

[0012] Furthermore, the two-stage heating reduction process in S3 comprises the following steps: First, the pellets are placed in a heating furnace, preheated at 900-1100°C for 1-2 hours, then heated to 1300-1500°C, and kept warm for 3-5 hours for deep reduction. After the reduction is completed, a reaction product is obtained; during the deep reduction process, argon gas is introduced into the heating furnace, and the flow rate of argon gas is controlled at 0.5-2L / min.

[0013] Furthermore, the density of the slag phase in S4 is measured to be 2.7-2.9 g / cm 3 .

[0014] Furthermore, in the electroslag remelting refining treatment in S4, the current is 500-1000A, the voltage is 20-40V, and the refining time is 1-3h.

[0015] Furthermore, the purity of the refined metallic chromium in S4 is 98.9% to 99.4%, and the recovery rate of chromium is 82.2% to 82.5%.

[0016] Beneficial effects of the present invention: The present invention provides a method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method. The present invention recycles and utilizes waste chromium-containing refractory materials as resources, thereby reducing the landfill of waste chromium-containing refractory materials and the serious safety risks caused by adding waste chromium-containing refractory materials as recycled aggregates to newly manufactured refractory materials to high-temperature and high-pressure kilns.

[0017] Specifically, the present invention subjects waste chromium-containing refractory materials to crushing and magnetic separation, acid leaching and impurity removal, carbon reduction, slag-gold separation and electroslag refining processes, and the purity of the metallic chromium finally produced reaches 98.9% to 99.4%, and the chromium recovery rate reaches 82.2% to 82.5%.

[0018] First, the present invention removes magnetic substances (mainly iron compounds) in waste chromium-containing refractory materials by magnetic separation; then, the present invention dissolves and removes magnesium compounds in chromium-containing enriched materials and soluble impurities on the surface by acid leaching; then, the present invention selects yttrium-stabilized zirconia and lanthanum oxyfluoride as additives, and yttrium-stabilized zirconia (YSZ; Y2O3:ZrO2=8:92mol%) forms oxygen vacancy defects at high temperatures, promotes O²⁻ migration of SiO2, and accelerates the formation of silicate melts. At the same time, the acidic characteristics of ZrO2 in yttrium-stabilized zirconia can selectively adsorb Fe³+ impurities, thereby facilitating the removal of silicon compounds and iron compounds. Then, lanthanum oxyfluoride (LaOF) undergoes La³+→La²+ valence change during carbothermal reduction, and electron transfer promotes Cr³+→Cr 0Reduction, the synchronously released F⁻ can combine with Mg²+ to generate MgF2 (melting point 1261℃), avoiding magnesium impurities from entering the metal phase. In addition, the present application accidentally discovered during the research process that the combination of LaOF and YSZ has a synergistic effect. Specifically, when used in combination, LaOF and YSZ can form a La-Zr-OF composite melt, and the slag phase density is reduced to 2.7-2.9g / cm³, which significantly improves the slag-gold separation efficiency, thereby significantly improving the purity of the final product metallic chromium; the present invention then uses a two-stage heating reduction process combined with inert gas protection to effectively avoid the problems of impurity mixing and chromium oxidation in the traditional single high-temperature reduction process, greatly improving the purity and yield of metallic chromium; finally, the present invention uses electroslag remelting technology to deeply remove impurities, so that the purity of metallic chromium is qualitatively improved. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The mass ratio of raw material composition of chromium-containing refractory varies greatly depending on the type of chromium-containing refractory. Specifically, chromium oxide Cr2O3 accounts for about 10% to 92% in different waste refractory; magnesium oxide MgO accounts for about 0% to 45% in different waste refractory; aluminum oxide Al2O3 accounts for about 2% to 85% in different waste refractory; silicon oxide SiO2 accounts for about 0% to 5% in different waste refractory; iron oxide Fe2O3 accounts for about 0% to 5% in different waste refractory, as well as other unmeasurable impurities and moisture.

[0021] The present invention collects waste chromium-containing refractory materials. After testing, the chromium content (mass percentage) in the waste chromium-containing refractory materials is 23.1% to 23.5%, the magnesium content (mass percentage) is 41.0% to 42.2%, the aluminum content (mass percentage) is 4.7% to 5.0%, the silicon content (mass percentage) is 2.5% to 2.7%, and the iron content (mass percentage) is 2.0% to 2.1%.

[0022] Example 1 A method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method, comprising the following steps: Raw material pretreatment: crush the above-mentioned waste chromium-containing refractory materials to a particle size of 0.1 mm, then remove the magnetic substances therein by magnetic separation, preliminarily separate the chromium-containing enriched material, and then perform acid leaching to remove impurities on the chromium-containing enriched material. Specifically, first, soak the chromium-containing enriched material in an acetic acid solution with a pH of 4.5 for 0.5 h to obtain an impurity-removed enriched material, then rinse the impurity-removed enriched material with deionized water until the washing water is neutral, and then dry it at 80°C for 12 h to obtain a chromium-rich raw material; Additive selection and ingredients: Yttrium-stabilized zirconium oxide and lanthanum oxyfluoride were selected as additives. Specifically, 100 kg of chromium-rich raw material, 25 kg of carbon powder (purity 99.5%; particle size 30 nm; purchased from Shanghai Yuanye Biotechnology Co., Ltd.), 4.2 kg of yttrium-stabilized zirconium oxide (purity 99.9%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) and 2.5 kg of lanthanum oxyfluoride (purity 99%; purchased from Inner Mongolia Zhongke Lancerium Rare Materials Technology Co., Ltd.) were mixed into a mixture according to the mass ratio; Carbon reduction method: the prepared mixture is pressed into pellets, and the diameter of the pellets is controlled at 20mm to ensure good air permeability and reaction activity. Then a two-stage heating reduction process is adopted. Specifically, the pellets are first placed in a heating furnace and preheated at 900°C for 1h to allow the carbonaceous reducing agent to react with the chromium-containing substance initially, and part of the chromium oxide is reduced. At the same time, the additive begins to play a role and reduces the melting point of the slag phase. Then the heating furnace is heated to 1300°C and kept warm for 3h for deep reduction. After the reduction is completed, a reaction product is obtained. During the deep reduction process, inert gas argon is introduced into the heating furnace, and the flow rate is controlled at 0.5L / min to create a reducing atmosphere, prevent chromium from being oxidized again, and improve the reduction rate of chromium. Slag-metal separation and refining: After the reduction is completed, the reaction product is cooled to 800°C. At this time, the slag phase and the metal phase have a good fluidity difference. The slag phase is initially separated and removed by gravity sedimentation (the density of the slag phase is determined to be 2.7g / cm 3 ), the metal phase obtained by preliminary separation (density measurement is 6.1g / cm 3 ) to obtain refined metallic chromium. Specifically, the refining process is performed by electroslag remelting technology. During the electroslag remelting process, the control current is 500A, the voltage is 20V, and the refining time is 1h. The electroslag remelting technology can deeply remove impurities, so that the purity of chromium in the refined metallic chromium is qualitatively improved; Product post-processing: The refined metallic chromium is cooled to room temperature and then packaged. It is packaged in a vacuum package or filled with inert gas to prevent the product from being oxidized during storage and transportation. The process of producing high-purity metallic chromium from waste chromium-containing refractory materials using the carbon reduction method is completed. After testing, the purity of the refined metallic chromium is 98.9% and the chromium recovery rate is 82.2%.

[0023] Example 2 A method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method, comprising the following steps: Raw material pretreatment: crush the above-mentioned waste chromium-containing refractory material to a particle size of 0.1 mm, then remove the magnetic material therein by magnetic separation, preliminarily separate the chromium-containing enriched material, and then perform acid leaching to remove impurities on the chromium-containing enriched material. Specifically, first, soak the chromium-containing enriched material in an acetic acid solution with a pH of 4.5 for 2 hours to obtain an impurity-removed enriched material, then rinse the impurity-removed enriched material with deionized water until the washing water is neutral, and then dry it at 100°C for 12 hours to obtain a chromium-rich raw material; Additive selection and ingredients: Yttrium-stabilized zirconium oxide and lanthanum oxyfluoride were selected as additives. Specifically, 100 kg of chromium-rich raw material, 30 kg of carbon powder (purity 99.5%; particle size 30 nm; purchased from Shanghai Yuanye Biotechnology Co., Ltd.), 4.5 kg of yttrium-stabilized zirconium oxide (purity 99.9%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) and 3 kg of lanthanum oxyfluoride (purity 99%; purchased from Inner Mongolia Zhongke Lancerium Rare Materials Technology Co., Ltd.) were mixed into a mixture according to the mass ratio; Carbon reduction method: the prepared mixture is pressed into pellets, and the diameter of the pellets is controlled at 20mm to ensure good air permeability and reaction activity. Then a two-stage heating reduction process is adopted. Specifically, the pellets are first placed in a heating furnace and preheated at 1100℃ for 2h to make the carbonaceous reducing agent and the chromium-containing substance react initially, and part of the chromium oxide is reduced. At the same time, the additive begins to play a role and reduces the melting point of the slag phase. Then the heating furnace is heated to 1420℃ and kept warm for 5h for deep reduction. After the reduction is completed, the reaction product is obtained. In the deep reduction process, inert gas argon is introduced into the heating furnace, and the flow rate is controlled at 1.5L / min to create a reducing atmosphere, prevent chromium from being oxidized again, and improve the reduction rate of chromium. Slag-metal separation and refining: After the reduction is completed, the reaction product is cooled to 850°C. At this time, the slag phase and the metal phase have a good fluidity difference. The slag phase is initially separated and removed by gravity sedimentation (the density of the slag phase is determined to be 2.8g / cm 3 ), the metal phase obtained by preliminary separation (density measurement is 6.1g / cm 3 ) to obtain refined metallic chromium. Specifically, the electroslag remelting technology is used for refining. During the electroslag remelting process, the control current is 800A, the voltage is 30V, and the refining time is 3h. The electroslag remelting technology can deeply remove impurities, so that the purity of chromium in the refined metallic chromium is qualitatively improved; Product post-processing: The refined metallic chromium is cooled to room temperature and then packaged. It is packaged in a vacuum package or filled with inert gas to prevent the product from being oxidized during storage and transportation. The process of producing high-purity metallic chromium from waste chromium-containing refractory materials using the carbon reduction method is completed. After testing, the purity of the refined metallic chromium is 99.4% and the chromium recovery rate is 82.5%.

[0024] Example 3 A method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method, comprising the following steps: Raw material pretreatment: crush the above-mentioned waste chromium-containing refractory material to a particle size of 1 mm, then remove the magnetic material therein by magnetic separation, preliminarily separate the chromium-containing enriched material, and then perform acid leaching to remove impurities on the chromium-containing enriched material. Specifically, first, soak the chromium-containing enriched material in an acetic acid solution with a pH of 6.0 for 2 hours to obtain an impurity-removed enriched material, then rinse the impurity-removed enriched material with deionized water until the washing water is neutral, and then dry it at 100°C for 12 hours to obtain a chromium-rich raw material; Additive selection and ingredients: Yttrium-stabilized zirconium oxide and lanthanum oxyfluoride were selected as additives. Specifically, 100 kg of chromium-rich raw material, 30 kg of carbon powder (purity 99.5%; particle size 30 nm; purchased from Shanghai Yuanye Biotechnology Co., Ltd.), 5 kg of yttrium-stabilized zirconium oxide (purity 99.9%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) and 3 kg of lanthanum oxyfluoride (purity 99%; purchased from Inner Mongolia Zhongke Lancerium Rare Materials Technology Co., Ltd.) were mixed into a mixture according to the mass ratio; Carbon reduction method: the prepared mixture is pressed into pellets, and the diameter of the pellets is controlled at 50mm to ensure good air permeability and reaction activity. Then a two-stage heating reduction process is adopted. Specifically, the pellets are first placed in a heating furnace and preheated at 1100°C for 2h to allow the carbonaceous reducing agent to react with the chromium-containing substance initially, and part of the chromium oxide is reduced. At the same time, the additive begins to play a role and reduces the melting point of the slag phase. Then the heating furnace is heated to 1500°C and kept warm for 5h for deep reduction. After the reduction is completed, a reaction product is obtained. During the deep reduction process, inert gas argon is introduced into the heating furnace, and the flow rate is controlled at 2L / min to create a reducing atmosphere, prevent chromium from being oxidized again, and improve the reduction rate of chromium. Slag-metal separation and refining: After the reduction is completed, the reaction product is cooled to 1000°C. At this time, the slag phase and the metal phase have a good fluidity difference. The slag phase is initially separated and removed by gravity sedimentation (the density of the slag phase is determined to be 2.9g / cm 3 ), the metal phase obtained by preliminary separation (density measurement is 6.1g / cm 3) to obtain refined metallic chromium. Specifically, the refining process is performed by electroslag remelting technology. During the electroslag remelting process, the control current is 1000A, the voltage is 40V, and the refining time is 3h. The electroslag remelting technology can deeply remove impurities and improve the purity of chromium in the refined metallic chromium; Product post-processing: The refined metallic chromium is cooled to room temperature and then packaged. It is packaged in a vacuum package or filled with inert gas to prevent the product from being oxidized during storage and transportation. The process of producing high-purity metallic chromium from waste chromium-containing refractory materials using the carbon reduction method is completed. After testing, the purity of the refined metallic chromium is 99.1% and the chromium recovery rate is 82.4%.

[0025] Comparative Example 1 Comparative Example 1 is the control group of Example 2, except that the yttrium-stabilized zirconia in Example 2 is replaced by conventional raw material calcium oxide (purity 99.9%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.), and the remaining raw materials, raw material amounts, steps, and parameters are kept consistent with those in Example 2, wherein the slag phase is initially separated and removed by gravity sedimentation, and the density of the slag phase is determined to be 3.3 g / cm 3 The density of the metal phase obtained by preliminary separation was determined to be 6.0 g / cm 3 , and then through refining and product post-processing, refined metallic chromium is finally obtained. After testing, the purity of refined metallic chromium is 91.7% and the chromium recovery rate is 73.3%.

[0026] Comparative Example 2 Comparative Example 2 is the control group of Example 2, in which the lanthanum fluoride oxide in Example 2 is replaced by conventional raw material calcium fluoride (purity 99.99%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.), and the remaining raw materials, raw material amounts, steps, and parameters are kept consistent with those in Example 2, wherein the slag phase is initially separated and removed by gravity sedimentation, and the density of the slag phase is determined to be 3.5 g / cm 3 The density of the metal phase obtained by preliminary separation was determined to be 6.0 g / cm 3 , and then through refining and product post-processing, refined metallic chromium is finally obtained. After testing, the purity of refined metallic chromium is 94.0%, and the chromium recovery rate is 77.6%.

[0027] Comparative Example 3 Comparative Example 3 is the control group of Example 2, except that the yttrium-stabilized zirconia in Example 2 is removed, and the remaining raw materials, raw material amounts, steps, and parameters are kept consistent with those in Example 2, wherein the slag phase is initially separated and removed by gravity sedimentation, and the density of the slag phase is determined to be 4.2 g / cm 3 The density of the metal phase obtained by preliminary separation was determined to be 5.9 g / cm 3, and then through refining and product post-processing, refined metallic chromium is finally obtained. After testing, the purity of refined metallic chromium is 77.2% and the chromium recovery rate is 53.4%.

[0028] Comparative Example 4 Comparative Example 4 is the control group of Example 2, in which the lanthanum fluoride oxide in Example 2 is removed, and the remaining raw materials, raw material amounts, steps, and parameters are kept consistent with those in Example 2, wherein the slag phase is initially separated and removed by gravity sedimentation, and the density of the slag phase is determined to be 4.0 g / cm 3 The density of the metal phase obtained by preliminary separation was determined to be 5.9 g / cm 3 , and then through refining and product post-processing, refined metallic chromium is finally obtained. After testing, the purity of refined metallic chromium is 80.7% and the chromium recovery rate is 55.1%.

[0029] Comparative Example 5 Comparative Example 5 is the control group of Example 2, in which the yttrium-stabilized zirconium oxide and lanthanum oxyfluoride in Example 2 are removed, and the remaining raw materials, raw material amounts, steps, and parameters are kept consistent with those in Example 2, wherein the slag phase is initially separated and removed by gravity sedimentation, and the density of the slag phase is determined to be 4.5 g / cm 3 The density of the metal phase obtained by preliminary separation was determined to be 5.7 g / cm 3 , and then through refining and product post-processing, refined metallic chromium is finally obtained. After testing, the purity of refined metallic chromium is 74.2% and the chromium recovery rate is 49.8%.

[0030] It should be noted that, in this article, terms such as "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or equipment that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment.

[0031] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the invention, and the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method, characterized in that: The following steps are involved: S1. Collect waste chromium-containing refractory materials and crush them to a particle size of 0.1-1 mm. After magnetic separation and impurity removal, a chromium-containing concentrate is obtained. After acid leaching and impurity removal, a chromium-rich raw material is obtained. S2, preparing a mixture of chromium-rich raw material, carbon powder, yttrium-stabilized zirconium oxide and lanthanum oxyfluoride; S3, pressing the mixture into pellets, and then subjecting the mixture to a two-stage heating reduction process to obtain a reaction product; S4, cooling the reaction product to 800-1000°C, and then preliminarily separating and removing the slag phase by gravity sedimentation, and subjecting the remaining metal phase to electroslag remelting and refining treatment to obtain refined metallic chromium, and completing the recovery of metallic chromium after cooling.

2. A method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method according to claim 1, characterized in that: The waste chromium-containing refractory materials described in S1 include the following components in terms of mass percentage: Chromium 23.1%~23.5%; Magnesium 41.0% to 42.2%; Aluminum 4.7%~5.0%; Silicon 2.5% to 2.7%; Iron 2.0%~2.1%.

3. The method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method according to claim 1, characterized in that: The acid leaching and impurity removal described in S1 includes the following steps: The chromium-containing concentrate is soaked in an acetic acid solution with a pH of 4.5 to 6.0 for 0.5 to 2 hours to obtain a de-impurity concentrate, and then the de-impurity concentrate is rinsed with deionized water until the washing water is neutral, and then dried at 80 to 100° C. for 12 hours to obtain a chromium-rich raw material.

4. The method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method according to claim 1, characterized in that: The purity of the carbon powder described in S2 is 99.5%; The purity of the yttrium-stabilized zirconia reaches 99.9%; The purity of the lanthanum oxyfluoride is up to 99%.

5. The method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method according to claim 1, characterized in that: The mass ratio of the chromium-rich raw material, carbon powder, yttrium-stabilized zirconium oxide and lanthanum oxyfluoride in S2 is 100:25-30:4.2-5.0:2.5-3.

0.

6. The method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method according to claim 1, characterized in that: The diameter of the pellets in S3 is 20 to 50 mm.

7. The method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method according to claim 1, characterized in that: The two-stage heating reduction process described in S3 includes the following steps: firstly placing the pellets into a heating furnace, preheating at 900-1100°C for 1-2h, then heating to 1300-1500°C, keeping warm for 3-5h for deep reduction, and obtaining a reaction product after the reduction is completed; during the deep reduction process, introducing argon gas into the heating furnace, and the flow rate of argon gas is controlled at 0.5-2L / min.

8. The method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method according to claim 1, characterized in that: The density of the slag phase in S4 was measured to be 2.7-2.9 g / cm 3 .

9. The method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method according to claim 1, characterized in that: In the electroslag remelting refining treatment in S4, the current is 500-1000A, the voltage is 20-40V, and the refining time is 1-3h.

10. The method for producing high-purity metallic chromium from waste chromium-containing refractory materials using a carbon reduction method according to claim 1, characterized in that: The purity of the refined metallic chromium described in S4 is 98.9% to 99.4%, and the recovery rate of chromium is 82.2% to 82.5%.

Citation Information

Patent Citations

  • Method for separating and recycling vanadium and chromium from vanadium and chromium-containing material

    CN104388683A

  • Method for preparing coarse granularity chromium carbide powder

    CN108046259A

  • Process for the production of high purity chromium

    DE69228988D1

Cited By

  • Resourceful treatment method of waste refractory material

    CN120796719A

  • A method for recycling waste refractory materials

    CN120796719B